Exploring the views of peri-operative nurses regarding efficient operating theatre room preparation in a selected private hospital - Filmalter, Cecilia Jacoba (University of Pretoria, 2023)
Dissertation (MNurs (Nursing Administration))--University of Pretoria, 2023.